Pelatihan Pembuatan Nirmana pada SMA Swasta Swabinakarya - Suprianingsih Suprianingsih; Desipriani Desipriani; Ahmad Khairian (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
Nirmana is the organization or arrangement of visual art elements such as dots, lines, colors, planes, space and texture into a harmonious whole. Nirmana can also be interpreted as the result of wishful thinking in the form of two-dimensional/flat nirmana (two dimensions) and three-dimensional nirmana/space (three dimensions) which must have high aesthetic and aesthetic values. Nirmana (Basic Forms) is a science that studies various things related to perception, space, shape, color, and materials that are in the form of two dimensions or three dimensions. The basic elements of two-dimensional shapes are triangles, rectangles, circles and organic shapes, while the basic elements of three-dimensional shapes are blocks, prisms, spheres and irregular shapes.